George Vernon Denny papers - Denny, George Vernon, 1899-1959.
Correspondence, memoranda, reports, speeches, writings, financial records, research notes, awards, printed matter, and photographs documenting Denny's career. Part I relates chiefly to the activities of International Seminars and Town Meetings, Inc., during the period (1958-1959) when Denny was its president, the organization's inter-American seminars held in eight South American cities in 1958, public forums, and the People-to-People organization. Also includes material on his work with the Office of War Information and his organization of the Niagara Frontier Convocation. Part II documents Denny's role as moderator (1935-1952) of the radio broadcasts of "America's Town Meeting of the Air." Correspondents include Sherman Adams, Norman P. Auburn, Charles Dana Bennett, Robert S. Byfield, George Catlin, Elizabeth S. Colclough, Norman Cousins, Milton Eisenhower, Hubert H. Humphrey, Foy D. Kohler, Cyrille Makinsky, Karl Mundt, Harriet F. Pilpel, Philip D. Reed, Edward Scofield, John Sparkman, Frank Stanton, and Charles E. Wilson.
appropriate custodial divisions of the Library of Congress.
Educator, radio personality, and organization executive.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Sherman, -- 1899-1986 -- Correspondence; Auburn, Norman P. -- 1905- -- Correspondence; Bennett, Charles Dana -- Correspondence; Byfield, Robert S. -- 1896-1955 -- Correspondence; Catlin, George Edward Gordon, -- Sir, -- 1896-1979 -- Correspondence; Colclough, Elizabeth S. -- Correspondence; Cousins, Norman -- Correspondence; Eisenhower, Milton Stover, -- 1899-1985 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Kohler, Foy D. -- Correspondence; Makinsky, Cyrille -- Correspondence; Mundt, Karl E. -- 1900-1974 -- Correspondence; Pilpel, Harriet F. -- Correspondence; Reed, Philip D. -- Correspondence; Scofield, Edward -- Correspondence; Sparkman, John, -- 1899-1985 -- Correspondence; Stanton, Frank, -- 1908-2006 -- Correspondence; Wilson, Charles Erwin, -- 1890-1961 -- Correspondence; International Seminars and Town Meetings, Inc; People-to-People (Organization); United States. -- Office of War Information; America's town meeting of the air (Radio program); Forums (Discussion and debate); Meetings -- New York (State) -- Buffalo; Radio addresses, debates, etc; South America -- Foreign relations -- United States; United States -- Foreign relations -- South America; Educators; Executives; Radio personalities